Multiscale Analysis of Cement Composites - Iwona Pokorska; Mariusz Poński; Tadeusz Burczyński (Computer assisted methods in engineering and science, 2024)
This paper is devoted to multiscale modeling of cement composites. The need for such an approach is due to the heterogeneous complex internal structure of the composite. A multiscale model of the composite was built and the results of computer simulations for the adopted parameters of the microstructure of the composite were presented, enabling a more detailed analysis of its mechanical and structural properties.